Assessing economic impact of tick-borne diseases and their control: the case of theileriosis immunisation - Mukhebi, A.W. (International Livestock Research Institute, 1996)
This paper first discusses the need to assess the economic impact of livestock diseases and their control. It then examines the conceptual framework for assessing the economic impact of diseases and their control. This is followed by a brief explanation of some of the economic concepts behind the control of livestock diseases. A computer spreadsheet model which has been used in the past for assessing ex-ante the economic impact of theileriosis and its alternative control by the infection-and-treatment method is explained. The data requirements for the model are discussed. Examples of the application of the model in various case studies and some of the results obtained are discussed briefly as an illustration of the type of information that the model can generate for disease control decision-making. The presentation ends by highlighting some of the issues that need to be addressed to facilitate assessments of the economics of tick-borne diseases.